Screening of Barley Germplasm and Released Cultivars against Stripe Disease (Drechslera graminea) under Artifical Inoculation Condition - KUMAR, VIRENDRA (Journal of Cereal Research, 2018)
An experiment was conducted during Rabi 2016-17 and 2017-18, in Rajasthan Agricultural Research Institute, Durgapura, Jaipur. Stripe disease (Drechslera graminea) cause significant losses to barley production in major barley growing countries. Resistance breeding programme of the crop is one of best eco-friendly management strategy. In the present study, 40 germplasms and 13 released varieties were screened under artificial inoculation condition. Out of 53 germplasms and released varieties, one release variety RD-2035 was found highly susceptible. Two genotypes were found susceptible namely BD-1717 and BD-1722. Four germplasms and five release varieties were found moderate susceptible. Eighteen germplasms and six release varieties were categorized as moderate resistant. Eleven germplasms were assessed as resistant and BD-1716, BD-1726, BD-1731, BD-1735, BD-1743, BD-1744 were recorded as highly resistant. Therefore, resistant germplasms could be used as a source of resistance to stripe disease for varietal development of barley. Â Key words: Stripe disease, Drechslera graminea, eco-friendly, screened, germplasms, varieties